A daily diary study of relationships between feelings of gratitude and well-being. Issue 4 (4th July 2017) - Nezlek, John B.; Newman, David B.; Thrash, Todd M.
Abstract: Much of the research on relationships between gratitude and well-being has concerned between-person level relationships, and this research suggests that increasing people's feelings of gratitude can increase their well-being. To complement this research, we examined such relationships at the within-person level. Participants ( N = 130) in the present study described their well-being and how grateful they felt each day for two weeks. MLM analyses found that at the within-person level, daily feelings of gratitude and hedonic and eudaimonic well-being were positively related. Lagged analyses found that feelings of gratitude on one day were positively related to hedonic (but not eudaimonic) well-being on the next day, and well-being on one day was not related to gratitude on the next day. These results complement existing research and suggest that causal relationships between gratitude and well-being may vary as a function of whether gratitude is measured in more affective or cognitive terms.